Theoretical assessment design at a South African school of nursing: A multimethod qualitative exploration - Gabieba Donough; Katlego Mthimunye; Felicity Daniels (PLoS ONE, 2026)
Introduction Theoretical assessment design is crucial in nursing education, ensuring students develop cognitive and problem-solving skills for clinical practice. However, misalignment with learning outcomes and inconsistent cognitive level distribution remain complex issues. Methods and findings This multimethod qualitative study explored theoretical assessment design in a South African nursing school through in-depth interviews with nurse educators and a document review of moderators’ reports. Stratified purposive sampling ensured diverse representation across National Qualifications Framework Levels 5–8. Data saturation was reached after nine interviews, analysed using Creswell and Creswell’s six-step thematic framework. The document review analysed 70 moderation reports (22 internal and 48 external) from 2015 to 2019, focusing on feedback related to final theoretical assessments. Content analysis, following Krippendorff’s framework, was used to identify themes and patterns. Findings revealed an overemphasis on lower-order cognitive skills (Bloom’s taxonomy), inconsistent question distribution, and misalignment with national qualification standards. Educators acknowledged these issues but cited time constraints, inadequate training, and institutional pressures as contributing factors. Moderation reports confirmed assessment inconsistencies, emphasising the need for better alignment with constructive alignment principles. Triangulation of data highlighted a gap between perceived best practices and actual assessment quality, suggesting assessments do not fully support higher-order cognitive skill development. Conclusion To improve the validity and reliability of theoretical assessments, nursing programmes should prioritise training in assessment design, strengthen alignment with learning outcomes, and implement moderation strategies to address inconsistencies. These findings contribute to the broader discourse on improving assessment practices in nursing education globally.